Totally unofficial : the autobiography of Raphael Lemkin - Lemkin, Raphael, 1900-1959 (Yale University Press, 2013)
"Among the greatest intellectual heroes of modern times, Raphael Lemkin lived an extraordinary life of struggle and hardship, yet altered international law and redefined the world's understanding of group rights. He invented the concept and word "genocide" and propelled the idea into international legal status. An uncommonly creative pioneer in ethical thought, he twice was nominated for the Nobel Peace Prize. Although Lemkin died alone and in poverty, he left behind a model for a life of activism, a legacy of major contributions to international law, and--not least--an unpublished autobiography. Presented here for the first time is his own account of his life, from his boyhood on a small farm in Poland with his Jewish parents, to his perilous escape from Nazi Europe, through his arrival in the United States and rise to influence as an academic, thinker, and revered lawyer of international criminal law"--